Factors Affecting Sticky Cost in Non-cyclical Consumer Companies in Indonesia - Nirely Wijaya, Monifa; Frederica, Diana (Jurnal Akuntansi, 2025)
This study aims to determine the effect of assets intensity, Good Corporate Governance, and audit quality on sticky cost. Type of data used was secondary data sourced from the company’s financial statement from www.idx.co.id. The population in this study are consumer non-cylicals companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The method of determining the sample in this study used purposive sampling method. The data analysis method that used multiple linear regression with Eviews 12 software. The results of this research show that Good Corporate Governance has a significant positive effect on sticky cost. Meanwhile, assets intensity, and audit quality has no significant effect on sticky cost.